Role of pegaptanib sodium in the treatment of neovascular age-related macular degeneration - Sobha Sivaprasad (Dove Medical Press, 2008)
Sobha SivaprasadLaser and Retinal Research Unit, King’s College Hospital, UKAbstract: Age-related macular degeneration (AMD) is responsible for more than half the blind registration in the United Kingdom. Retinal manifestations of AMD can be categorized as either atrophic or neovascular. The hallmark of AMD is the development of choroidal neovascularization (CNV). Until recently, there have been few, limited treatment modalities (eg, photodynamic therapy [PDT]) for this condition and the mainstay of treatment has comprised social and lifestyle support. However, increased understanding of the molecular processes at work in neovascular AMD and CNV in recent years has led to the introduction of new antiangiogenic agents that target vascular endothelial growth factor (VEGF). These agents either inhibit a selected VEGF isoform (eg, VEGF165 inhibition by pegaptanib sodium) or inhibit all forms of the VEGF isoform (eg, non-selective VEGF blockade by ranibizumab). The trial data suggest that non-selective inhibition of VEGF offers better treatment outcomes in neovascular AMD. As a result, agents that inhibit all VEGF isoforms are now widely used as first-line therapy for this condition. However, it is known that VEGF plays an important role in maintaining the intergrity of the cardiovascular system and, particularly as the age of patients with AMD places them at an elevated risk of thromboembolic events, long-term post-marketing surveillance data are essential to determining whether non-selective VEGF blockade confers any increased risk. Theoretically, selective VEGF inhibition may reduce any risk associated with pan-VEGF blockade, yet on the basis of initial trials, their use remains more limited at this time. However, clinical practice suggests that initial trials may have under-estimated the efficacy of selective-VEGF inhibition. Observational studies also indicate that better treatment outcomes may be possible by combining VEGF inhibitors sequentially with each other, or with existing therapies (eg, photodynamic therapy [PDT]). The optimum role and indications of anti-VEGF agents will come through careful consideration of the available efficacy and safety data, from the outcomes of long-term follow-up studies, and through assessment of the relative merits of the two approaches to VEGF inhibition in clinical practice. At this time, further head-to-head trials, and economic evaluations, comparing the treatment alternatives are needed.Keywords: age-related macular degeneration (AMD), choroidal neovascularization (CNV), vascular endothelial growth factor (VEGF), cardiovascular, ranibizumab, pegaptanib sodium